Medicolegal Perspective on Physician-Induced Demand Issue - Wulandari Berliani Putri; Vita Widyasari; Juliet Musabula; Muhammad Jihadul Hayat (Administrative Law Departement Faculty of Law Universitas Sebelas Mare, 2021)
Physician-Induced Demand has long been a topic in the field of health science. However, compared to medical error or malpractice, PID receives less attention. The term PID itself is not recognized in Indonesian health regulations, but does it mean that the law permits it? This question is essential because the medical law insists that doctors perform medical efforts following professional standards and standard operating procedures. Physician-Induced Demand disguises an action that may manipulate and harm the patient's best interest. This study aims to shed light on the extent to which the medical law protects patients' rights from Physician-Induced Demand conduct. This study employs a juridical and normative approach. Primary resources were collected by investigating health regulations, while secondary resources were obtained from electronic databases. The result of this study shows that PID is a medical action against the will of law. Medical law requires that medical treatment be based on sound principles, such as following high-quality standards, honesty, fairness, humanity, nondiscrimination, efficiency, and effectiveness. Physician-Induced Demand, which tends to the interests of a physician, is opposed to those legal principles. Therefore, this study argues that Physician-Induced Demand violates the principles of medical law. It should be avoided under any circumstances.